Glutaraldehyde and Glyoxal Crosslinked Polyethylenimine for Copper Ion Adsorption from Water. Issue 9 (1st March 2022) - Swamy, Azekah Yashna; Prasad, Shelvin; Pan, Xun; Andersson, Mats R.; Gedefaw, Desta
Abstract: The water body can potentially be contaminated with heavy metals such as Cu 2+ ions which beyond a certain concentration could impact human and animal health. In the past, different techniques have been developed to remove Cu 2+ ions from water. In this study, polyethlenimine (PEI) was crosslinked with glutaraldehyde and glyoxal to yield three polymers (P1‐P3). P3 consists of hydroxypropyl methylcellulose (HPMC) as a template to decrease the size of the crosslinked polymer particles. The polymer powders were used to adsorb Cu 2+ from CuSO4 water solutions. The addition of 50, 100 and 150 mg of P3 removed 25, 32 and 38 mg of Cu 2+, respectively, from 0.075 M (10 mL) of CuSO4 solution, after stirring at room temperature for 24 h. In comparison, P1 and P2 removed a lower amount. The better performance of P3 arises from the larger surface area of the polymer powder compared to P1 and P2 as revealed from scanning electron microscopy (SEM) images. Kinetic studies indicated that the polymers remove a larger amount of Cu 2+ during the first 3 h with a slower rate of adsorption continuing until 12 h. The adsorption kinetics were fitted with Elovich and Pseudo second order models to understand the adsorption mechanism. The higher R 2 (∼0.99) value of the linear plots signifies the adsorption is likely to follow a Pseudo second order kinetics, with P3 showing a rate constant of 8.43x10 −5  g mg −1 min −1 . The Cu 2+ loaded polymers (100 mg) were soaked in 10 mL of 2 % HNO3 for 24 h for the desorption of Cu 2+, where 12, 10 and 16 mg of Cu 2+ desorbed from P1, P2 and P3, respectively. This indicates the polymers could potentially be reused to adsorb another batch of Cu 2+ from water to maximize an economic benefit. Abstract : Polyethylenimine (PEI) was crosslinked with either gluteraldehyde or glyoxal with or without the presence of hydroxypropyl methylcellulose (HPMC) to yield polymer powders. The polymers were used to remove Cu 2+ from water and the effect of factors such as contact time, temperature and quantity of polymer on adsorption were monitored using uv‐visible spectroscopy.